Effect of harvesting time on yield and yield attributes of chickpea (Cicer arietinum L.) (Bangladesh Journal of Agricultural Research, 2010)
Field experiments were carried out during 2004-2006 at Bangladesh Agricultural Research Institute Farm in Grey Terrace Soils, Agro-Ecological Zone (AEZ 28), Joydebpur, Gazipur, Bangladesh to determine the effects of harvesting time on yield and yield attributes of chickpea. Chickpea seeds of three varieties viz., BARI Chola-5, BARI Chola-6, and BARI Chola-8 were collected at three times viz., i) when the pods were yellowish with a few yellow greens (H1 stage), ii) when most of the pods were light brown with a few yellow (H2 stage), and iii) when all the pods were completely brown and dry (H3 stage). All the seeds were stored in earthen pot until conducting the field study. Significant variation was not observed in three varieties of chickpea for most of the parameters studied. The highest pods/plant, seeds/pod, and seed yield were observed in BARI Chola-5 and the lowest in BARI Chola-8. Seeds collected at the stage when most of the pods were light brown with a few yellow (H2 stage) recorded the highest pods/plant, seeds/pod, 1000-seed weight and seed yield. The highest seed yield was recorded from BARI Chola-5 when seeds were collected at H2 stage. Keywords: Chickpea; harvesting time; yield; yield attributes. DOI: 10.3329/bjar.v35i1.5875Bangladesh J. Agril. Res. 35(1) : 143-148, March 2010